dy/dt for ln x =e^y+(x^2+y^3)^2-2 if x=1 y=0 and dx/dt=-2

Thank you for the opportunity to help you with your question!

dy/dt (ln x )= dy/dt [e^y+(x^2+y^3)^2-2]

dy/dt (ln x )= dy/dt [e^y+(x^4+y^6+ 2 x^2 y^2 )-2]

0 = e^y * dy/dt + y^6 * dy/dt + 2 x^2 y^2 *dy/dt

putting value of x and y

0 = e^0 * dy/dt + 0^6 * dy/dt + 2 *1^2 *0^2 *dy/dt

dy/dt = 0

dx/dt=-2

dy/dx= (dy/dt ) (dx/dt)

dy/dx = 0* -2

dy/dx = 0

-------------------------------------------------------------------------------------------------------------------------------------------------

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up